PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI PT. PARIKESIT SRI PUTRA - Fitriyah, Yosi Aenul; Hikmah, Hikmah (SCIENTIA JOURNAL, 2021)
This study aims to analyze the effect of product quality and promotion on purchasing decisions at PT Parikesit Sri Putra. This research was conducted on consumers of PT Parikesit Sri Putra. The data used in this study is primary data obtained by distributing questionnaires to the respondents. The sample in this study has as many as 295 respondents with a sampling technique that is accidental sampling. Data analysis used multiple linear regression analysis with the help of IBM SPSS 25. The results of this study indicate that product quality has a positive and significant effect on purchasing decisions, promotions have a positive but not significant effect on purchasing decisions, product quality and promotion simultaneously affect purchasing decisions.